2018
DOI: 10.1111/jftr.12295
|View full text |Cite
|
Sign up to set email alerts
|

The State of Family Research and Social Media

Abstract: Social media has changed the ways we create and consume information, as well as the ways we interact with others. In the current review, findings from the existing literature on family and social media are considered, hypotheses about the ways social media is influencing families now and will do so in the future are proposed, and suggestions for future research to move the field forward are posited. More specifically, the existing literature on family relationships and technology use, as well as the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 86 publications
0
37
0
1
Order By: Relevance
“…Additionally, MTurk workers can be hired to write reviews, descriptions, and blog entries for websites; provide editing and transcription; rate the accuracy of search engine results; provide feedback about videos and photos, advertisements, other media and recruitment flyers, and program descriptions; or provide feedback about whether people or materials in photos are appropriate, relatable, and culturally sensitive. They can also tag photos or videos with keywords that practitioners can use to recruit a particular audience (Dworkin, Brar, Hessel, & Rudi, 2016). …”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
“…Additionally, MTurk workers can be hired to write reviews, descriptions, and blog entries for websites; provide editing and transcription; rate the accuracy of search engine results; provide feedback about videos and photos, advertisements, other media and recruitment flyers, and program descriptions; or provide feedback about whether people or materials in photos are appropriate, relatable, and culturally sensitive. They can also tag photos or videos with keywords that practitioners can use to recruit a particular audience (Dworkin, Brar, Hessel, & Rudi, 2016). …”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
“…Our mixed-method study focuses on screen time among US young adults, recursively analyzing qualitative interviews collected in 2018 and nationally representative, longitudinal cohort data collected from 2007 to 2017 to inductively build, test, and refine a conceptual framework articulating influences on young adults’ contemporary technology use . Responding to researchers’ calls to integrate principles from the life course perspective ( Elder, 1994 ) to improve our understanding of technology use ( Dworkin et al, 2018 ), we asked whether and how life course principles can help us to understand variation in young adults’ technology use. We found that a life course lens is fundamental for understanding young adults’ technology use in two ways.…”
Section: Introductionmentioning
confidence: 99%
“…The life course perspective is a particularly promising theoretical tool for understanding how technology shapes people’s lives. As Dworkin, Rudi, and Hessel (2018, 807) have argued, “Life course theory is particularly well suited to understanding [the] many influences on family and social media. Life course allows for the analysis of individuals’ lives in structural, social, and cultural contexts.” Technology use varies substantially across ages, historical periods, and cultures, making a life course lens particularly salient ( Dworkin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing research on family use of technology focuses on the frequency of technology use and the types of technology being used, often attempting to categorize different types of use (Dworkin, Rudi, & Hessel, ; Rudi, Walkner & Dworkin, ). Fewer studies have considered the quality of the interactions using technology and the cascading implications of communication using technology for family development.…”
mentioning
confidence: 99%